PENGARUH PENERAPAN BAHAN AJAR BERMUATAN NILAI-NILAI KARAKTER DENGAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) PADA MATERI USAHA DAN GERAK HARMONIS TERHADAP HASIL BELAJAR KELAS XI SMAN 7 PADANG - Cici Ramayanti; Masril Masril; Yenni Darvina (PILLAR OF PHYSICS EDUCATION, 2016)
Not optimal relationship obtained learners is caused by using strategy/method that not exactly in learning. Beside of that, teaching material that used does explain characters that need to reach by learners. A solution to solving the problem is needed teaching materials charged character values and learning strategy that can increase learners’s thinking ability. This research is a quasi-experimental with study design only randomized control group design. The population of research was eleventh grade students of SMAN 7 Padang in the academic year 2014/2015. Sampling are used with a technique cluster random sampling, so there are two sampel class, which is XI MIA5 as experiment class and XI MIA3 as control class. The  research instrumental is written tests for cognitive, format of observation for affective and performance sheet for psychomotor. The data analysis technique used  two average similar test at significance level 0.05 The research shows the average values consecutive of  experimental class are 88,24 at cognitive, 79,41 at affective, and 80,48 at psychomotor. The average values of control class consecutive are 77,71 at cognitive, 72,49 at affecive, and 70,16 at   psychomotor. It shows that the average values of experiment class are higher than control class. From data analysis is got tcount at cognitive, affective, and psychomotor consecutive are 3,38, 3,31, 4,93 and ttabel 2,00. It shows that tcount are bigger than ttabel. it can be said that there are difference learning outcomes between experiment class and control class at significance level o,o5, which is learning outcomes of experiment class are bigger than control class. Difference learning outcomes is caused by effect of the application of teaching materials charged character values with Learning Strategy Increased Ability To Think  on work  and harmonic motion. It can be concluted that there are effects o the application of teaching materials charged character values with Learning Strategy Increased Ability To Think on work and harmonic motion at class XI of SMAN 7 Padang.